Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1902/jop.1999.70.10.1234
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Gingival Fibroblasts on Bioabsorbable Regenerative Materials In Vitro

Abstract: These results suggest that cell carrier membranes could affect RGF morphology and thus alter gingival tissue healing following GTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 11 publications
4
19
1
1
Order By: Relevance
“…In the present study, HGFs were chosen in order to get results closer to normal phenotype behavior in comparison with immortal cell lines (Fukuda et al 2000;Hillmann et al 2002;Locci et al 1997;Payne et al 1996;Simain-Sato et al 1999). Optical microscopy of the bottoms of wells and SEM analysis of the Inion membranes lower face confirmed the absence of cells and a positive barrier effect until 13 weeks, while the manufacturer states an 8-12 weeks in vivo barrier effect.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, HGFs were chosen in order to get results closer to normal phenotype behavior in comparison with immortal cell lines (Fukuda et al 2000;Hillmann et al 2002;Locci et al 1997;Payne et al 1996;Simain-Sato et al 1999). Optical microscopy of the bottoms of wells and SEM analysis of the Inion membranes lower face confirmed the absence of cells and a positive barrier effect until 13 weeks, while the manufacturer states an 8-12 weeks in vivo barrier effect.…”
Section: Discussionmentioning
confidence: 84%
“…The use of GTR has proved to be a suitable technique when simulating regeneration, new connective tissue attachment and bone formation [17]. When a membrane is placed between the denuded root surface and the repositioned mucogingival flap, it provides a secluded space into which fibroblasts and osteogenic cells from the healthy apical portion of the periodontium may migrate [15].…”
Section: Discussionmentioning
confidence: 99%
“…GBR sites with well‐integrated unexposed barriers during healing exhibited significantly better bone regeneration than sites with non‐integrated, exposed barriers 40,41 . Adequate tissue integration capacity seems to be intimately related to surface topography, porosity, and chemical composition of the implanted biomaterial 30‐34 . In vitro culture studies have suggested that surface texture, protein binding capacity, and chemical composition influence cellular functions, such as attachment, spreading, morphology, and migration over barrier membranes 23‐26,30‐34 .…”
Section: Discussionmentioning
confidence: 99%